Tingkat Partisipasi Anggota KWT Mawar dalam Program Harum Madu di Desa Karangtengah, Kecamatan Kadungora, Kabupaten Garut: The Participation Level of KWT Mawar Members in the Harum Madu Program in Karangtengah Village, Kadungora Sub-District, Garut Regency - Af'idah, Rivianty Putri Nur; Abubakar, Abubakar; Budiandrian, Bayu (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2024)
The Halaman Rumah Masyarakat Terpadu (Harum Madu) program, initiated by the Garut Regency government, aims to ensure household-level food self-sufficiency. Based on BPS data (2023), agricultural land in Kadungora District is very limited, making the Harum Madu program a viable solution for optimizing yard land. This study aimed to analyze respondent characteristics and the participation level of KWT Mawar members in the Harum Madu program. A quantitative descriptive analysis was used, with sampling conducted through a census of all 40 KWT Mawar members. Results indicated that most KWT Mawar members are aged 34-44 years, have an elementary school education, work as housewives, have 1-3 family dependents, and an average household income of Rp.1,500,000-Rp.2,000,000. The participation level of KWT Mawar members in the Harum Madu program is moderate, with a score of 1485. Participation in decision-making falls under the moderate category, while participation in implementation and utilization of results is high. Meanwhile, participation in evaluation is in the moderate category.